AVALIAÇÃO DA BIOMASSA DE FUNGOS AMAZÔNICOS COMO FONTE DE LIPASES PARA BIOCATÁLISE - Israel P. Romano (Química Nova)
We evaluated the biomass of twenty Amazonian fungal isolates as a potential source of mycelium-bound lipases with hydrolytic, synthetic or enantioselective activity for biocatalysis application. We compared the hydrolytic activity of three biomass treatments (delipidated, non-delipidated and cultivated in medium without inducer). Delipidated biomass showed better results in the hydrolysis of p-nitrophenyl palmitate compared to the other two treatments for fifteen isolates. Delipidated biomass of six Aspergillus strains and UEA_115 strain showed a high synthesis activity of ethyl palmitate by transesterification in organic medium. Results were confirmed by spectrophotometry (410 nm) and gas chromatography. In this reaction, the isolate DPUA_1539 A. flavo-furcatis reached a maximum value of 668.5 ± 23.5 mU g-1. Enantioselective activity assays indicated that biomass-bound lipases from UEA_115 isolate (E = 3.58; ees = 7 ± 0) and in particular from the DPUA_1539 A. flavo-furcatis isolate (E = 24.15; ees = 91 ± 1) have the ability to discriminate enantiomers of the drug ibuprofen by ester synthesis, preferably with (R)-enantiomer. These results encourage further investigations of these fungi as potential lipase suppliers for biocatalytic processes such as biodiesel production and enantiopure drugs.